Multidimensional Nature of Grief: A Social Health Perspective on Grief-Related Loneliness - Kösesoy, Berra Cansız (Lut TAMAM, 2026)
This narrative review focuses on the multidimensional nature of grief and examines grief-related loneliness from the perspectives of psychiatry and social work. The study is based on the premise that loneliness experienced during the grief process is not an individual deficiency but a social health problem produced and reinforced by social and institutional structures. Within this framework, grief is considered not only as an individual emotional response but also as a biopsychosocial process shaped by social support networks, social norms, and structural inequalities. The review addresses the psychiatric conceptualization of grief, the relationship between grief-related loneliness, social isolation, and mental health, and the role of social work in supporting individuals during the grief process. It also evaluates the need for integration between psychiatric interventions and social work practices and discusses the limitations of current approaches. In addition, the grief experiences of vulnerable populations and the social risks they face are examined, including individuals living alone, older adults, people with chronic or terminal illnesses, migrants and refugees, and LGBT individuals. The study highlights the similarities and differences between psychiatric and social work perspectives and proposes a framework for interdisciplinary integration. The findings suggest that comprehensive responses to grief-related loneliness require integrated intervention models that combine psychiatric and social work approaches and place social health at the center.

Bu araştırma, yasın çok boyutlu doğasını merkeze alan, yas ile yalnız kalma deneyimini psikiyatri ve sosyal hizmet yaklaşımları ekseninde değerlendiren anlatısal bir derleme niteliğindedir. Araştırmanın problem odağı; “yasın ardından deneyimlenen yalnızlığın, bireysel bir eksiklik değil sosyal ve kurumsal yapılar tarafından üretilerek pekiştirilen bir sosyal sağlık sorunu olduğu” iddiasıdır. Bu kapsamda yas, yalnızca bireysel bir tepki olarak değil, biyopsikososyal süreçler bağlamında değerlendirilmiştir. Yas süreci ve tedavisi, sosyal destek mekanizmaları, toplumsal normlar ve yapısal eşitsizlikler odağında ele alınmıştır. Ayrıca, yasın psikiyatrik kavramsallaştırması, yalnızlık ve sosyal izolasyonun yas ile ilişkisi, sosyal sağlık açısından yas, sosyal hizmetin yas süreçlerindeki rolü, psikiyatrik müdahaleler ile sosyal hizmet uygulamalarının bütünleşme ihtiyacı ve mevcut uygulamalardaki sınırlılıkları tartışılmıştır. Yalnız yaşayanlar, yaşlılar, kronik ve ölümcül bir hastalığı olanlar, göçmen ve mülteciler ile LGBT bireyler gibi farklı dezavantajlı grupların yas süreçlerindeki deneyimleri ve karşılaştıkları sosyal riskler değerlendirilmiştir. Psikiyatri ve sosyal hizmet yaklaşımlarının, yas süreçlerine ilişkin benzer ve farklı yönleri ortaya konularak disiplinlerarası entegrasyon için bir çerçeve sunulmuştur. Bu doğrultuda, yas ile yalnız kalma deneyiminin kapsamlı bir şekilde ele alınabilmesi için psikiyatri ve sosyal hizmet temelli yaklaşımları bütünleştiren, sosyal sağlığı merkeze alan müdahale modellerinin geliştirilmesi gerektiği sonucuna ulaşılmıştır.
Yasın Çok Boyutlu Doğası: Yasla İlişkili Yalnızlığa Sosyal Sağlık Perspektifinden Bir Bakış
Keywords: Social Psychology; Sosyal Psikoloji